Komitmen Sumber Daya Manusia Sektor Publik Berbasis Kepemimpinan Spiritual Melalui Spiritualitas Di Tempat Kerja - I G.G Oka Pradnyana; I Made Purba Astakoni; Ni Made Satya Utami (Widya Manajemen, 2020)
This study has several objectives namely; analyze the influence of spiritual leadership on organizational commitment; analyze the influence of spiritual leadership on spirituality in the workplace; analyze the influence of spirituality at work on organizational commitment; analyze the role of spirituality in the workplace as a mediator on the influence of spiritual leadership on organizational commitment. The population in this study were all employees of drinking water companies in the Badung Regency, Tabanan Regency, and PAM Denpasar City, which totaled 902 employees. Sampling was done purposively with a total of 200 respondents. Data collection techniques used were interviews with questionnaires with multiple choice closed. In this study data analysis using the Partial Least Square (PLS) approach. The results showed that the overall evaluation of the model seen from the coefficient of determination can be said to be quite good, Q-Square Predictive Relevance meets existing requirements and Goodness of Fit in a large position then the overall model is quite good. The first hypothesis, which states that spiritual leadership has a significant positive effect on organizational commitment, is not yet acceptable. The second hypothesis, which states that spiritual leadership has a significant positive effect on spirituality at work, is acceptable. The third hypothesis, which states that spirituality at work has a significant positive effect on organizational commitment, is acceptable. Based on testing through the Sobel test, it can be explained that spirituality in the workplace can act as a mediator concerning spiritual leadership to organizational commitment.